Morphological and Histopathological Changes in Kidney and Suprarenal Glands in Hanging and Sudden Death – An Autopsy Based Study - Ghosh, Soma; Saha, Souvik; Kundu, Sanchita Das (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Suicide by hanging mode is fourth leading cause of death; the majority in low and middle-income countries. Stress plays a key role in structural and functional changes in suprarenal glands and kidneys. Objective: To identify morphological and histopathological changes in kidney and suprarenal gland in hanging and correlating those changes with acute or chronic stress. Methods: This cross-sectional, descriptive study was conducted on 108 cases of hanging and sudden death collected from the Department of Forensic & State Medicine of a medical college in India, based on inclusion and exclusion criteria. All macroscopic and microscopic changes in kidneys and suprarenal glands were recorded. Results: Most of the cases belonged to the 21–40 years age group; a male predominance was observed and most of the cases were from the rural areas. The length of kidney, cortical thickness, tubular necrosis decrease in chronic stress but increase in acute. Surface haemorrhage, congested interstitium, congested glomerulus increase in chronic and acute stress but cloudy degeneration, tubular cast, interstitial oedema decrease in chronic and acute stress. Suprarenal gland weight, thickness, capsular haemorrhage, congestion, sinusoidal dilation, lipid depletion increase in chronic and acute stress, but necrosis decrease. Nodular hyperplasia decrease in chronic stress but increase in acute. Oedema decreased in acute stress but increased in chronic stress. Conclusion: Differences in morphological and histopathological changes in kidney and suprarenal gland were observed in acute and chronic stress conditions. International Journal of Human and Health Sciences Vol. 09 No. 04 Oct’25 Page: 257-264